Localized scleroderma – classification and tools used for the evaluation of tissue damage and disease activity/severity - Wolska-Gawron, Katarzyna; Krasowska, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2017)
Localized scleroderma is a rare autoimmune disorder affecting the dermis, subcutaneous tissue and deeper structures. The course of localized scleroderma includes three stages: early inflammation, progressive sclerosis and atrophy. The active stage of the disease is characterized by erythema (‘lilac ring’), skin induration, and appearance of new or expansion of pre-existing skin lesions during the preceding month. The most recent localized scleroderma classification recognizes five types of the disease: localized, generalized, linear, deep and mixed. Various methods have been proposed for the evaluation of disease activity or severity and tissue damage, including ultrasonography, thermography, durometry, computed tomography and magnetic resonance imaging. However, all of them have their limitations, as they only make it possible to assess one component of the disease: activity or severity or tissue damage. The LS Cutaneous Assessment Tool (LoSCAT) questionnaire is a promising method of patient evaluation because of its availability, repeatability of results and sensitivity to changes resulting from treatment.